PERAN BUDAYA ORGANISASIONAL MEMODERASI PENGARUH MOTIVASI DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA GURU (STUDI PADA GURU MTs SE KECAMATAN KEDUNGWUNI KABUPATEN PEKALONGAN) (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to determine the role of organizational culture moderates the influence of motivation and organizational commitment on MTs teachers performance in Kedungwuni districtof Pekalongan regency. Research was conducted MTs teachers in Kedungwuni district as many as 141 people using the population research. The statistical analyze used by the validity test,reliability test, normality test, classical assumptions, goodness of fit model and hypothesis test. Based on the survey results revealed that the motivation significant and positive impact onteachers performance; organizational commitment significant and positive impact on teachers performance; organizational culture significant and positive impact on teachers performance;organizational culture strengthen the effect of motivation on teachers performance and organizational culture strengthen the influence of organizational commitment to teachers performanceKeywords : motivation, organizational commitment, organizational culture, and the performance of teachers.